2014
DOI: 10.4161/hv.27967
|View full text |Cite
|
Sign up to set email alerts
|

The internet’s role in HPV vaccine education

Abstract: T he internet is the second most popular source, after healthcare providers, of information regarding human papillomavirus (HPV). These online searches usually begin with the user entering generic terms in the search engine, and then reading the first few results that the engine returns. Unfortunately, research shows that much of this information obtained about the HPV vaccine is inaccurate and incomplete. In this review, we summarize the literature pertaining to online information concerning the HPV vaccine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Having grown up in a time of easy internet access, teenagers and young adults can surf the web with ease; thus, finding information related to HPV would not be challenging. The internet is the second most popular source of information, after health care providers, for information regarding HPV . Private surfing permits adolescents, teens, and young adults to search for information that otherwise might not be acceptable by family and church members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having grown up in a time of easy internet access, teenagers and young adults can surf the web with ease; thus, finding information related to HPV would not be challenging. The internet is the second most popular source of information, after health care providers, for information regarding HPV . Private surfing permits adolescents, teens, and young adults to search for information that otherwise might not be acceptable by family and church members.…”
Section: Resultsmentioning
confidence: 99%
“…The internet is the second most popular source of information, after health care providers, for information regarding HPV. 33 Private surfing permits adolescents, teens, and young adults to search for information that otherwise might not be acceptable by family and church members. Harvey et al 34 Young adults in our study often incorrectly identified cancers associated with HPV, and most were unaware of the prevalence of HPV in society.…”
Section: Discussionmentioning
confidence: 99%
“…These results expand on the assertion by Patel et al that healthcare providers should be educated on what information is available on the internet: healthcare providers should also understand what information would be accessible to the average reader. 8 Previous studies of HPV information on the internet have focused on whether the text encouraged or discouraged parents from vaccinating their children. 5 Our results suggest that further research is warranted to compare popular pro-vaccination and anti-vaccination websites based on readability.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of information sources on HPV infection has been demonstrated through numerous studies which showed that individuals gathering information from the Internet had a higher level of knowledge and were more likely to accept HPV vaccine [ 30 , 31 ]. Healthcare professionals shared medical information with their patients and the general public using social media.…”
Section: Discussionmentioning
confidence: 99%